Chemical oscillations in catalytic CO oxidation reaction - Bzovska, I.S.; Mryglod, I.M. (Condensed Matter Physics, 2010)
Temporal dynamics of a heterogeneous catalytic system, namely of the catalytic CO oxidation on Pt(110) surface at low pressures, is investigated with taking into account the adsorbate-driven structural transformations of the catalyst surface. Uniform temporal periodic chemical oscillations of the CO and oxygen coverages, and the fraction of the surface of the 1 x 1 structure are obtained in a narrow region of phase diagram between two uniform stable states of high and low catalytic activities, respectively.